Faraday effect in CoPt-CaF2 nanogranular films with hard magnetic property for magnetic-field-free faraday devices - Kobayashi, Nobukiyo; Iwasa, Tadayoshi; Ikeda, Kenji; Arai, Ken-Ichi (Frontiers in Physics, 2022)
Magneto-optical Faraday devices, such as optical isolators, require a structure to apply a magnetic field to the incorporated magneto-optical material. The application of a magnetic field hinders the miniaturization and integration of these devices. Nanogranular films show Faraday rotation angles up to 40 times larger than Bi-YIG in the optical communication band (1550 nm). Nanogranular films are submicron-to several-micrometer-thick and contribute to the miniaturization and integration of optical devices. Here, we introduce CoPt–CaF2 nanogranular films exhibiting a magnetic-field-free magneto-optical Faraday effect, which are Co3Pt alloy that are hard magnets with residual magnetization. These nanogranular films exhibit the Faraday effect without requiring a magnetic field owing to their residual magnetization.